Travel route and formation optimization for flocks of drones in package delivery by using an ACO based V-Shape algorithm - De Kuyffer, E.; Joseph, W.; Martens, L.; De Pessemier, T. (Results in engineering, 2024)
Despite a lot of research throughout the last half century about the fact that geese and other bird species have the tendency to fly in a V-Shape configuration, investigation about applying this phenomenon to swarms of drones used in parcel delivery is limited. The extensive increase in online shopping and the resulting intensified package transport have urged the importance to optimize travel routes and swarms configurations in order to reduce the energy needed to carry out these tasks by the use of drones. To minimize the amount of energy needed by a swarm to travel an optimized distance, an Ant Colony Optimization (ACO) based V-Shape algorithm is applied on different configurations of swarms, each with a different drag coefficient, a distinctive surface opposite to drag, and a separate energy recovery parameter. For groups of up to 10 drones it is best to move in a V-Shape, being a 37.3% better configuration for 4 drones and 15.7% more efficient for 9 drones than the next best, being the vertical line formation. For larger groups of 10 drones or more, the vertical line becomes the most energy efficient being 22.3% more (energy) efficient than the V-Shape for 16 drones and 38.6% more (energy) efficient for 25 drones.